Synthesis and Characterization of an Energetic Compound (E)-4,4’-bis(tert-Butyl-N,N,O-azoxy)-3,3’-diazenofurazan - An, Lili; Yu, Qianqian; Sun, Chufeng (Asian Journal of Chemistry, 2013)
A furazan-based energetic compound (E)-4,4'-bis(tert-butyl-N,N,O-azoxy)-3,3'-diazenofurazan (BADF) was synthesized and characterized by NMR, FT-IR spectroscopy and elemental analyses. The single crystal structure analysis revealed the symmetric BADF molecule adopted an E-configuration with respect to azo group -N=N- and the torsion angle of N(2)-C(1)-N(1)-N(1)# is 161.97º. The planes defined by two furazan rings are parallel and their distance is only 0.404 (2) Å. In the crystal structure, only van der Waals forces but obvious p–p stacking were observed. Intramolecular C–H···O hydrogen bonds forming two S(6) ring further stabilized the supramolecular sheet structure.